Aspek Hukum Pelayanan Publik Berbasis Online Melalui Simadu (Sistem Informasi Manajemen Desa Terpadu) - Kurniasih, Dewi; Hassanah, Hetty; Fidowaty, Tatik; Yulianto, Heri Dwi; Setiyadi, Angga (Abdimas Indonesian Journal, 2024)
This study aims to provide in-depth knowledge for partners/community of Margahayu District, Bandung Regency through legal advocacy related to the use of Simadu (Integrated Village Management Information System) as a means of public service. The method used is the lecture method and legal advocacy related to the legal aspects of online-based public services through Simadu as well as participatory methods to explore various problems found in the field. Legal advocacy to village and sub-district officials in the Margahayu District, Bandung Regency because the use of Simadu does not rule out the possibility of legal problems, so that all village and sub-district officials really need legal advice to anticipate and resolve legal problems that arise due to the use of Simadu such as related data personal.